Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/ajo.13052
|View full text |Cite
|
Sign up to set email alerts
|

Decisions to consent for autopsy after stillbirth: Aboriginal and Torres Strait Islander women's experiences

Abstract: Background:The stillbirth rate for Australian Aboriginal and Torres Strait Islander infants is twice that for non-Indigenous infants. Autopsy is the gold standard for fetal investigation; however, parental consent is often not given. There is little research investigating the drivers of parents' decision-making for autopsy after stillbirth. Aims: The current study explored the reasons why Aboriginal and Torres StraitIslander women did or did not give permission to autopsy after stillbirth. Materials and Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…More recently, studies have found evidence of significant health economic effects associated with these events (42,51,87). Affected families are motivated to obtain an explanation for the fetal or perinatal death, at least in part, to know how likely it is to happen in future pregnancies (27).…”
Section: Risk To Mothermentioning
confidence: 99%
“…More recently, studies have found evidence of significant health economic effects associated with these events (42,51,87). Affected families are motivated to obtain an explanation for the fetal or perinatal death, at least in part, to know how likely it is to happen in future pregnancies (27).…”
Section: Risk To Mothermentioning
confidence: 99%
“…While autopsy is the gold standard for understanding the cause of stillbirth, parents often manifest discomfort and concerns in its acceptance; parents feel shocked, distressed, unprepared and overwhelmed by their grief [10,11]. Therefore, they may be not able to provide their consent for fetal examination.…”
Section: Introductionmentioning
confidence: 99%
“…Caregivers need to be prepared for the difficulty of speaking about autopsy with parents [10]. Parents feel afraid and distressed about the procedure [11] and they have wrong concerns about disfigurement and dismemberment [10,11,14]. Unfortunately, this barrier against fetal autopsy is sometimes related to caregivers' disinformation and misconceptions.…”
Section: Introductionmentioning
confidence: 99%
“…There is little accurate data across states to inform care for these women and families, and very few autopsies are conducted to enhance understanding of causation of stillbirth or potential risk factors. 12 In the current pilot study, we sought to identify Aboriginal and Torres Strait Islander stillbirth rates, risk factors and causes in the regional, rural and remote catchment of the TUH.…”
Section: Introductionmentioning
confidence: 99%